Method for preparing battery-grade iron phosphate by using surfactant
By using the surfactant CTAB in the preparation of lithium iron phosphate materials, the process flow is simplified and batch stability is improved, and the problems of long reaction cycles and cumbersome steps in the prior art are solved, and lithium iron phosphate materials with high compaction density and good electrochemical properties are achieved.
Patent Information
- Application Number
- CN202411974967.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art has problems such as long reaction cycles, cumbersome steps, and poor batch stability when preparing lithium iron phosphate materials, making it difficult to effectively improve the compaction density and energy density of the material.
The surfactant cetyl trimethylammonium bromide (CTAB) was used as the regulator to prepare battery-grade iron phosphate materials by co-precipitation method, simplifying the process flow and improving batch stability.
The high compaction density and good electrochemical properties of lithium iron phosphate materials have been achieved, with a discharge performance of 0.1C reaching 155.46 mAh/g and a discharge capacity of 1C reaching 130.07 mAh/g, which is suitable for large-scale production.
Smart Images

Figure CN119683588A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery materials, and in particular to a method for preparing battery-grade iron phosphate by using a surfactant. Background Art
[0002] As the penetration rate of new energy vehicles continues to increase, the booming power battery market has increasingly stringent requirements on the energy density of lithium iron phosphate, while the capacity and voltage platforms of lithium iron phosphate are close to their theoretical values, and there is little room for improvement. Therefore, improving the compaction density of lithium iron phosphate has become an effective way to improve the energy density of lithium iron phosphate. At present, on the material side, the way to improve the compaction density of lithium iron phosphate is mainly to grade the particle size of the iron phosphate precursor by various methods.
[0003] The Chinese patent document with the publication number CN118702083A discloses a method for preparing an iron phosphate precursor suitable for high-pressure compacted lithium iron phosphate. Based on amorphous ammonium iron phosphate with a specific primary particle size, by changing the frequency and stirring rate of the ultrasonic generator in batches during the crystallization reaction, the degree of agglomeration of secondary particles in the crystallization process can be simply and effectively intervened, so that the particle size range and proportion of the obtained secondary iron phosphate dihydrate particles are stable and controllable, and then iron phosphate dihydrate I, iron phosphate dihydrate II and iron phosphate dihydrate III of different particle size ranges are mixed in a certain proportion to achieve large and small particle grading. However, the large-scale industrialization of the ultrasonic generator, which is crucial in this process, faces many difficulties, and the process has the disadvantages of long process cycle and low production capacity.
[0004] The Chinese patent document with publication number CN 118324108A discloses "A kind of ferric phosphate and its preparation method and application", which controls the particle size range and ratio of the obtained ferric phosphate dihydrate secondary particles by subjecting the obtained amorphous ammonium ferric phosphate slurry to two-stage crystallization treatment and adjusting the ratio of the two-stage crystallization slurry. Obviously, the key technical point of this process lies in the distribution ratio of the two-stage crystallization slurry, and the process window is small, which is prone to poor batch stability.
[0005] However, the above technologies all regulate the microstructure and particle size distribution of iron phosphate materials in a step-by-step manner, which has disadvantages such as long reaction cycle, complicated steps, and poor batch stability. Summary of the invention
[0006] In view of the shortcomings of the prior art such as complex reaction steps, long reaction cycle, poor batch stability, etc., the present invention provides a method for preparing battery-grade iron phosphate using a surfactant to improve the conductivity and compaction density of lithium iron phosphate materials. The preparation method is simple and feasible, has good batch stability, and is suitable for large-scale production. The details are as follows: A method for preparing battery-grade iron phosphate using a surfactant comprises the following steps: S1, respectively prepare a ferrous salt solution, a phosphate salt solution, a 10-25 wt% hydrogen peroxide solution, a 1-10 wt% hexadecyltrimethylammonium bromide (CTAB) aqueous solution and a 60-85 wt% phosphoric acid solution, and set aside; S2, after adjusting the pH of the ferrous salt solution to 2.0-2.5, adding a CTAB aqueous solution to obtain a mixed solution of ferrous salt and CTAB; S3, after adjusting the pH value of the phosphate solution to 6.0-8.0 with concentrated sulfuric acid, adding a hydrogen peroxide solution to obtain a phosphorus-oxygen mixed solution; S4. Under continuous stirring, gradually heating the mixed solution of ferrous salt and CTAB obtained in step S2 to 40-60° C., adding the mixed solution of phosphorus and oxygen obtained in step S3, and simultaneously adding a CTAB aqueous solution, so that all ferrous ions are gradually oxidized to trivalent ferrous ions, and obtaining slurry A after reacting for 60 min; S5, slurry A is initially filtered and washed to obtain filter cake A; S6. Under continuous stirring conditions, add pure water to the filter cake A and continue stirring until the slurry is uniform, control the mass ratio of pure water to filter cake to be 1.2-1.8:1, then add phosphoric acid solution, and then heat to 80-100 °C. After the slurry color changes to white, keep warm for 60-120 min to obtain white slurry B; S7. After slurry B is filtered, washed and dried, dihydrate iron phosphate is obtained. After the dihydrate iron phosphate is calcined, high-purity battery-grade anhydrous iron phosphate is obtained.
[0007] Moreover, in the step S1, the concentration of phosphorus in the phosphate solution is 0.8-1.4 mol / L; the phosphate solution is prepared from ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, phosphoric acid, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate.
[0008] Moreover, in the step S1, the concentration of iron in the ferrous salt solution is 0.8-1.3 mol / L; the ferrous salt solution is prepared from ferrous sulfate, ferrous nitrate, ferrous chloride, iron powder and iron sheet.
[0009] Moreover, in the step S2, the mass ratio of the added ferrous salt to the CTAB in the ferrous salt solution and the CTAB aqueous solution is 100-200:1.
[0010] Moreover, in step S3, concentrated ammonia water is used to adjust the pH of the phosphate solution to 6.0-8.0; when the pH is less than 5.0, a certain amount of concentrated ammonia water needs to be added; the molar ratio of the added hydrogen peroxide to the ferrous element in the ferrous salt solution should be controlled to be 0.6-0.8:1.
[0011] Moreover, in the step S4, the phosphorus-oxygen mixed solution is added within 30-60 minutes; the molar ratio of iron element to phosphorus element in the ferrous salt and CTAB mixed solution and the phosphorus-oxygen mixed solution is 1:0.9-1.1.
[0012] Moreover, in the step S5, the conductivity of the washing water of the slurry A after preliminary filtration and washing is ≤2000 μS / cm.
[0013] Moreover, in step S6, the molar ratio of phosphorus in the added phosphoric acid solution to iron in the slurry A solution should be controlled to be n(P):n(Fe)=0.1-0.5:1; and the heating time is controlled to be 90-110 min.
[0014] Moreover, the filtering, washing, drying, and calcining methods and equipment described in step S7 are commonly used methods or equipment in existing iron phosphate preparation technologies; the conductivity of the washing water of slurry B after filtering and washing needs to be ≤400 μS / cm.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. In the preparation process of the present invention, CTAB aqueous solution (hexadecyltrimethylammonium bromide) is added as a surfactant. First, CTAB is a cationic surfactant. The cationic hydrophilic group is adsorbed on the surface of the primary particles due to the charge attraction, and the hydrophobic chain is outward, surrounding the primary particles. The primary particles are hindered from agglomerating due to the repulsive force of the hydrocarbon chain, thereby achieving the purpose of inhibiting the agglomeration of primary and secondary particles. Secondly, CTAB has a strong effect on Fe in an acidic system. 3+ It has a certain control effect, and thus has a good control ability in the crystal nucleation stage; 2. The present invention provides a method for preparing battery-grade iron phosphate using a surfactant, which uses ferrous salt and CTAB solution as a base solution, a mixed solution of phosphate and hydrogen peroxide, and a CTAB aqueous solution as a feeding solution. It is a preparation method for synthesizing iron phosphate using a trivalent iron solution Fenton system. Since the product primary particles have rich internal pores, the lithium iron phosphate material obtained after grinding and one sintering can ensure that the powder compaction density reaches a high level of 2.55 g / cc, and a certain amount of small particles provide better electrical properties. The 0.1C discharge performance reaches 155.46 mAh / g, and the 1C discharge capacity reaches 130.07 mAh / g; 3. The present invention does not require precise control of the reaction pH, does not require customization of special reaction equipment, and only requires the addition of a small amount of surfactant (CTAB). The battery-grade iron phosphate material with a composite structure of large and small particles can be prepared by a co-precipitation method, which is suitable for industrial production; 4. The present invention avoids the problems of long reaction cycle and complicated steps caused by the step-by-step regulation of the microscopic morphology and particle size distribution of the iron phosphate material in the prior art. In the preparation process, by controlling the reaction conditions and adding a certain amount of surfactant (CTAB), the uniform growth of the iron phosphate particles and the effective control of the particle size are achieved without the need for complicated post-processing steps; 5. The present invention adds a surfactant (CTAB) during the preparation process, which effectively improves the dispersibility and uniformity of the iron phosphate particles, reduces the particle agglomeration phenomenon, and thus improves the batch stability of the product; 6. The present invention has excellent repeatability. The data of ferric phosphate dihydrate and anhydrous ferric phosphate obtained through a large number of experiments are very stable, which proves that the process window of the present invention is large and suitable for industrial production; 7. The raw materials required by the present invention, such as phosphoric acid and CTAB, are not used in large quantities and are cheap and readily available, and are suitable for industrial production; 8. The present invention utilizes CTAB to regulate the synthesis stage of the process, rather than other surfactants. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The scanning electron micrographs of the iron phosphate dihydrate prepared in Experiment 1, where 1(a) is a 50 k scanning electron micrograph and 1(b) is a 10 k scanning electron micrograph; Figure 2 The scanning electron micrographs of the iron phosphate dihydrate prepared in Experiment 2, where 2(a) is a 50 k scanning electron micrograph and 2(b) is a 10 k scanning electron micrograph; Figure 3 Scanning electron micrographs of iron phosphate dihydrate prepared in Experiment 3, where 3(a) is a 50 k scanning electron micrograph and 3(b) is a 10 k scanning electron micrograph. DETAILED DESCRIPTION
[0017] Example 1 A method for preparing battery-grade iron phosphate using a surfactant comprises the following steps: S1, respectively prepare a ferrous salt solution, a phosphate solution, a 10 wt% hydrogen peroxide solution, a 1 wt% CTAB solution and a 60 wt% phosphoric acid solution for standby use; S2, after adjusting the pH of the ferrous salt solution to 2.0, adding a CTAB aqueous solution to obtain a mixed solution of ferrous salt and CTAB; S3, after adjusting the pH value of the phosphate solution to 6.0 with concentrated sulfuric acid, adding a hydrogen peroxide solution to obtain a phosphorus-oxygen mixed solution; S4. Under continuous stirring, gradually heating the mixed solution of ferrous salt and CTAB obtained in step S2 to 40° C., adding the mixed solution of phosphorus and oxygen obtained in step S3, and simultaneously adding a CTAB aqueous solution, so that all ferrous ions are gradually oxidized to trivalent ferrous ions, and obtaining slurry A after reacting for 60 min; S5, slurry A is initially filtered and washed to obtain filter cake A; S6. Under continuous stirring conditions, pure water was added to the filter cake A and the mixture was continuously stirred until the slurry was uniform. The mass ratio of pure water to filter cake was controlled to be 1.2:1. Then, phosphoric acid solution was added and the mixture was heated to 80°C. After the slurry color changed to white, the mixture was kept warm for 60 minutes to obtain white slurry B. S7. After slurry B is filtered, washed and dried, dihydrate iron phosphate is obtained. After the dihydrate iron phosphate is calcined, high-purity battery-grade anhydrous iron phosphate is obtained.
[0018] Furthermore, in step S1, the concentration of phosphorus in the phosphate solution is 0.8 mol / L; the phosphate solution is prepared from ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, phosphoric acid, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate.
[0019] Furthermore, in step S1, the concentration of iron in the ferrous salt solution is 0.8 mol / L; the ferrous salt solution is prepared from ferrous sulfate, ferrous nitrate, ferrous chloride, iron powder and iron sheet.
[0020] Furthermore, in step S2, the mass ratio of the added ferrous salt to the CTAB in the ferrous salt solution and the CTAB aqueous solution is 100:1.
[0021] Furthermore, in step S3, concentrated ammonia water is used to adjust the pH of the phosphate solution to 6.0; the molar ratio of the added hydrogen peroxide to the ferrous element in the ferrous salt solution should be controlled to be 0.6:1.
[0022] Furthermore, in step S4, the phosphorus-oxygen mixed solution is added within 30 minutes; and the molar ratio of iron element to phosphorus element in the ferrous salt and CTAB mixed solution and the phosphorus-oxygen mixed solution is 1:0.9.
[0023] Furthermore, in the step S5, the conductivity of the washing water of the slurry A after preliminary filtration and washing is ≤2000 μS / cm.
[0024] Furthermore, in step S6, the molar ratio of the phosphorus element in the added phosphoric acid solution to the iron element in the slurry A solution should be controlled to be n(P):n(Fe)=0.1:1; and the heating time is controlled to be 90 min.
[0025] Furthermore, the conductivity of the washing water of slurry B after filtering and washing needs to be ≤400 μS / cm.
[0026] Example 2 A method for preparing battery-grade iron phosphate using a surfactant comprises the following steps: S1, respectively prepare a ferrous salt solution, a phosphate solution, a 25 wt% hydrogen peroxide solution, a 10 wt% CTAB solution and an 85 wt% phosphoric acid solution for standby use; S2, after adjusting the pH of the ferrous salt solution to 2.5, adding a CTAB aqueous solution to obtain a mixed solution of ferrous salt and CTAB; S3, after adjusting the pH value of the phosphate solution to 8.0 with concentrated sulfuric acid, adding a hydrogen peroxide solution to obtain a phosphorus-oxygen mixed solution; S4. Under continuous stirring, gradually heating the mixed solution of ferrous salt and CTAB obtained in step S2 to 60° C., adding the mixed solution of phosphorus and oxygen obtained in step S3, and simultaneously adding a CTAB aqueous solution, so that all ferrous ions are gradually oxidized to trivalent ferrous ions, and obtaining slurry A after reacting for 60 min; S5, slurry A is initially filtered and washed to obtain filter cake A; S6. Under continuous stirring conditions, pure water was added to the filter cake A and the mixture was continuously stirred until the slurry was uniform. The mass ratio of pure water to filter cake was controlled to be 1.8:1. Then, phosphoric acid solution was added and the temperature was raised to 100°C. After the slurry color changed to white, the mixture was kept warm for 120 minutes to obtain a white slurry B. S7. After slurry B is filtered, washed and dried, dihydrate iron phosphate is obtained. After the dihydrate iron phosphate is calcined, high-purity battery-grade anhydrous iron phosphate is obtained.
[0027] Furthermore, in step S1, the concentration of phosphorus in the phosphate solution is 1.4 mol / L; the phosphate solution is prepared from ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, phosphoric acid, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate.
[0028] Furthermore, in step S1, the concentration of iron in the ferrous salt solution is 1.3 mol / L; the ferrous salt solution is prepared from ferrous sulfate, ferrous nitrate, ferrous chloride, iron powder and iron sheet.
[0029] Furthermore, in step S2, the mass ratio of the added ferrous salt to the CTAB in the ferrous salt solution and the CTAB aqueous solution is 200:1.
[0030] Furthermore, in step S3, concentrated ammonia water is used to adjust the pH of the phosphate solution to 8.0; the molar ratio of the added hydrogen peroxide to the ferrous element in the ferrous salt solution should be controlled to be 0.8:1.
[0031] Furthermore, in step S4, the phosphorus-oxygen mixed solution is added within 30-60 minutes; and the molar ratio of iron element to phosphorus element in the ferrous salt and CTAB mixed solution and the phosphorus-oxygen mixed solution is 1:1.1.
[0032] Furthermore, in the step S5, the conductivity of the washing water of the slurry A after preliminary filtration and washing is ≤2000 μS / cm.
[0033] Furthermore, in step S6, the molar ratio of phosphorus in the added phosphoric acid solution to iron in the slurry A solution should be controlled to be n(P):n(Fe)=0.5:1; and the heating time is controlled to be 110 min.
[0034] Furthermore, the filtering, washing, drying, and calcining methods and equipment described in step S7 are commonly used methods or equipment in existing ferric phosphate preparation technologies; the conductivity of the washing water of slurry B after filtering and washing needs to be ≤400 μS / cm.
[0035] Example 3 A method for preparing battery-grade iron phosphate using a surfactant comprises the following steps: S1, respectively prepare a ferrous salt solution, a phosphate solution, an 18 wt% hydrogen peroxide solution, a 5 wt% CTAB solution and a 70 wt% phosphoric acid solution for standby use; S2, after adjusting the pH of the ferrous salt solution to 2.2, adding a CTAB aqueous solution to obtain a mixed solution of ferrous salt and CTAB; S3, after adjusting the pH value of the phosphate solution to 7.0 with concentrated sulfuric acid, adding a hydrogen peroxide solution to obtain a phosphorus-oxygen mixed solution; S4. Under continuous stirring, gradually heating the mixed solution of ferrous salt and CTAB obtained in step S2 to 50° C., adding the mixed solution of phosphorus and oxygen obtained in step S3, and simultaneously adding a CTAB aqueous solution, so that all ferrous ions are gradually oxidized to trivalent ferrous ions, and obtaining slurry A after reacting for 60 min; S5, slurry A is initially filtered and washed to obtain filter cake A; S6. Under continuous stirring conditions, pure water was added to the filter cake A and the mixture was continuously stirred until the slurry was uniform. The mass ratio of pure water to filter cake was controlled to be 1.58:1. Then, phosphoric acid solution was added and the mixture was heated to 90°C. After the slurry color changed to white, the mixture was kept warm for 90 minutes to obtain white slurry B. S7. After slurry B is filtered, washed and dried, dihydrate iron phosphate is obtained. After the dihydrate iron phosphate is calcined, high-purity battery-grade anhydrous iron phosphate is obtained.
[0036] Furthermore, in step S1, the concentration of phosphorus in the phosphate solution is 1.1 mol / L; the phosphate solution is prepared from ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, phosphoric acid, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate.
[0037] Furthermore, in step S1, the concentration of iron in the ferrous salt solution is 1.1 mol / L; the ferrous salt solution is prepared from ferrous sulfate, ferrous nitrate, ferrous chloride, iron powder and iron sheet.
[0038] Furthermore, in step S2, the mass ratio of the added ferrous salt to the CTAB in the ferrous salt solution and the CTAB aqueous solution is 150:1.
[0039] Furthermore, in step S3, concentrated ammonia water is used to adjust the pH of the phosphate solution to 7.0; the molar ratio of the added hydrogen peroxide to the ferrous element in the ferrous salt solution should be controlled to be 0.7:1.
[0040] Furthermore, in the step S4, the phosphorus-oxygen mixed solution is added within 45 minutes; and the molar ratio of the iron element to the phosphorus element in the ferrous salt and CTAB mixed solution and the phosphorus-oxygen mixed solution is 1:1.0.
[0041] Furthermore, in the step S5, the conductivity of the washing water of the slurry A after preliminary filtration and washing is ≤2000 μS / cm.
[0042] Furthermore, in step S6, the molar ratio of the phosphorus element in the added phosphoric acid solution to the iron element in the slurry A solution should be controlled to be n(P):n(Fe)=0.3:1; and the heating time is controlled to be 100 min.
[0043] Furthermore, the filtering, washing, drying, and calcining methods and equipment described in step S7 are commonly used methods or equipment in existing ferric phosphate preparation technologies; the conductivity of the washing water of slurry B after filtering and washing needs to be ≤400 μS / cm.
[0044] Experimental Section
[0045] Experiment 1 This experiment adopts the technical solution of the present invention, a method for preparing battery-grade iron phosphate using a surfactant, comprising the following steps: Step 1: (1) Weigh 568.7 g of ammonium dihydrogen phosphate, dissolve it and dilute it to 2.53 L to obtain a phosphate solution; weigh 1337.1 g of ferrous sulfate heptahydrate, dissolve it and dilute it to 4.0 L to obtain a ferrous salt solution.
[0046] (2) Weigh 7.25 g of CTAB and add it directly into the above ferrous salt solution and slowly stir it evenly. Control the pH of the iron-titanium mixed solution to 2.20 by adding concentrated sulfuric acid solution.
[0047] (3) Under continuous stirring, concentrated ammonia water was added to the above phosphate salt solution in small amounts and in multiple times to control the pH value of the phosphate salt solution to 7.5, 327.0 g of 35 wt% hydrogen peroxide was directly added thereto, and finally pure water was added to make the volume to 3.53 L to obtain a phosphorus-oxygen mixed solution.
[0048] Step 2: (1) The ferrous mixed solution prepared in step 1 was heated to 50 °C, and the phosphorus-oxygen mixed solution was slowly added over 30 min under continuous stirring, and 7.25 g of CTAB aqueous solution was added at the same time.
[0049] (2) After the feeding is completed, a qualitative test is performed to determine whether all the ferrous ions have been oxidized to ferric ions; the reaction is then continued for 60 minutes to obtain slurry A.
[0050] (3) After the reaction is completed, the slurry A is preliminarily washed in a centrifuge and dried at high speed to obtain filter cake A.
[0051] Step 3: (1) Add pure water to the filter cake A obtained in step 2, continue stirring until the slurry is uniform, continue to add 166.0 g of 85 wt % phosphoric acid solution, then raise the temperature to 95 ° C and keep it warm for 90 min to obtain a white slurry B.
[0052] (2) After slurry B is filtered, washed and dried, dihydrate iron phosphate is obtained. After the dihydrate iron phosphate is calcined, high-purity battery-grade anhydrous iron phosphate is obtained.
[0053] Experiment 2 The difference between this experiment and experiment 1 is that the concentration of the phosphate solution is increased in step 1. The specific steps are as follows: Step 1: (1) Weigh 645.4 g of ammonium dihydrogen phosphate, dissolve it and dilute it to 2.53 L to obtain a phosphate solution; weigh 1337.1 g of ferrous sulfate heptahydrate, dissolve it and dilute it to 4.0 L to obtain a ferrous salt solution.
[0054] (2) Weigh 7.25 g of CTAB and add it directly into the above ferrous salt solution and slowly stir it evenly. Control the pH of the iron-titanium mixed solution to 2.20 by adding concentrated sulfuric acid solution.
[0055] (3) Under continuous stirring, concentrated ammonia water was added to the above phosphate salt solution in small amounts and in multiple times to control the pH value of the phosphate salt solution to 7.5, 327.0 g of 35 wt% hydrogen peroxide was directly added thereto, and finally pure water was added to make the volume to 3.53 L to obtain a phosphorus-oxygen mixed solution.
[0056] Step 2: (1) The ferrous mixed solution prepared in step 1 was heated to 50 °C, and the phosphorus-oxygen mixed solution was slowly added over 30 min under continuous stirring, and 7.25 g of CTAB aqueous solution was added at the same time.
[0057] (2) After the feeding is completed, a qualitative test is performed to determine whether all the ferrous ions have been oxidized to ferric ions; the reaction is then continued for 60 minutes to obtain slurry A.
[0058] (3) After the reaction is completed, the slurry A is preliminarily washed in a centrifuge and dried at high speed to obtain filter cake A.
[0059] Step 3: (1) Add a certain amount of pure water to filter cake A and continue stirring until the slurry is uniform. Then, add 166.0 g of 85 wt % phosphoric acid solution and heat to 95 °C and keep warm for 90 min to obtain white slurry B.
[0060] (2) After slurry B is filtered, washed and dried, dihydrate iron phosphate is obtained. After the dihydrate iron phosphate is calcined, high-purity battery-grade anhydrous iron phosphate is obtained.
[0061] Experiment 3 The difference between this experiment and experiment 2 is that the amount of CTAB added in step 1 is increased, and CTAB is not added in step 2. The specific steps are as follows: Step 1: (1) Weigh 645.4 g of ammonium dihydrogen phosphate, dissolve it and dilute it to 2.53 L to obtain a phosphate solution; weigh 1337.1 g of ferrous sulfate heptahydrate, dissolve it and dilute it to 4.0 L to obtain a ferrous salt solution.
[0062] (2) Weigh 14.5 g of CTAB and add it directly into the above ferrous salt solution and slowly stir it evenly. Control the pH of the iron-titanium mixed solution to 2.20 by adding concentrated sulfuric acid solution.
[0063] (3) Under continuous stirring, concentrated ammonia water was added to the above phosphate salt solution in small amounts and in multiple times to control the pH value of the phosphate salt solution to 7.5, 327.0 g of 35 wt% hydrogen peroxide was directly added thereto, and finally pure water was added to make the volume to 3.53 L to obtain a phosphorus-oxygen mixed solution.
[0064] Step 2: (1) The ferrous mixed solution prepared in step 1 is heated to 50°C, and the phosphorus-oxygen mixed solution is slowly added within 30 minutes under continuous stirring; (2) After the feeding is completed, a qualitative test is performed to determine whether all the ferrous ions have been oxidized to ferric ions; the reaction is then continued for 60 minutes to obtain slurry A.
[0065] (3) After the reaction is completed, the slurry A is preliminarily washed in a centrifuge and dried at high speed to obtain filter cake A.
[0066] Step 3: (1) Add a certain amount of pure water to filter cake A and continue stirring until the slurry is uniform. Then, add 166.0 g of 85 wt % phosphoric acid solution and heat to 95 °C and keep warm for 90 min to obtain white slurry B.
[0067] (1) After slurry B is filtered, washed and dried, dihydrate iron phosphate is obtained. After the dihydrate iron phosphate is calcined, high-purity battery-grade anhydrous iron phosphate is obtained.
[0068] The SEM images of the iron phosphate dihydrate prepared in Experiment 1-3 were scanned, and the results are shown in Figure 1-3 As shown, Figure 1 This is a scanning electron microscope image of iron phosphate dihydrate prepared in Experiment 1. Figure 2 This is the scanning electron microscope image of the iron phosphate dihydrate prepared in Experiment 2. Figure 3 This is a scanning electron microscope image of the iron phosphate dihydrate prepared in Experiment 3. From the scanning electron microscope image, it can be observed that the primary particles of the iron phosphate dihydrate prepared in Experiment 1 (the present invention) are aggregated into uniform flakes, and the flakes are stacked on each other to form a cluster structure; the primary particles of the iron phosphate dihydrate prepared in Experiment 2 are obviously more dispersed than the primary particles in Experiment 1, and the primary particles are aggregated into loose clusters; the primary particles of the iron phosphate dihydrate prepared in Experiment 3 are obviously more dispersed than the primary particles in Example 1, and the primary particles are stacked into loose irregular spheres.
[0069] Experiment 4 The anhydrous iron phosphate prepared in Experiments 1-3 was used as a precursor, ground and sintered once to make lithium iron phosphate material, and then made into a button battery. The powder compaction density and electrochemical properties were tested. The test results are shown in the following table.
[0070] Table 1 Performance test results of iron phosphate and lithium iron phosphate
[0071] As shown in Table 1, after the anhydrous iron phosphate prepared in Experiment 1 is made into lithium iron phosphate, its powder compaction density can reach 2.55 g / cm 3 , and the 0.1C and 1C discharge capacities are maintained at a high level; while the lithium iron phosphate prepared from anhydrous iron phosphate in Experiment 2, although the 1C discharge capacity can reach 130.46 mAh / g, its powder compaction density is only 2.50 mAh / g; the lithium iron phosphate prepared from anhydrous iron phosphate in Experiment 3, although the 1C discharge capacity can reach 132.58 mAh / g, its powder compaction density is only 2.45 g / cm 3It can be seen that Experiments 2 and 3 cannot maintain a balance between a higher powder compaction density and a higher discharge capacity of lithium iron phosphate, and the effect is worse than that of Experiment 1 (the present invention).
Claims
1. A method for preparing battery-grade iron phosphate using a surfactant, characterized in that: The following steps are involved: S1, respectively prepare a ferrous salt solution, a phosphate solution, a 10-25 wt% hydrogen peroxide solution, a 1-10 wt% CTAB solution and a 60-85 wt% phosphoric acid solution for standby use; S2, after adjusting the pH of the ferrous salt solution to 2.0-2.5, adding a CTAB aqueous solution to obtain a mixed solution of ferrous salt and CTAB; S3, after adjusting the pH value of the phosphate solution to 6.0-8.0, adding a hydrogen peroxide solution to obtain a phosphorus-oxygen mixed solution; S4, under continuous stirring, gradually heating the mixed solution of ferrous salt and CTAB obtained in step S2 to 40-60° C., adding the phosphorus-oxygen mixed solution obtained in step S3, and simultaneously adding a CTAB aqueous solution, so that all ferrous ions are gradually oxidized to trivalent ferrous ions, and obtaining slurry A after reacting for 60 min; S5, slurry A is initially filtered and washed to obtain filter cake A; S6. Under continuous stirring, add pure water to the filter cake A and continue stirring until the slurry is uniform, then add phosphoric acid solution, and then heat to 80-100 ° C. After the slurry color changes to white, keep warm for 60-120 min to obtain white slurry B; S7. After slurry B is filtered, washed and dried, dihydrate iron phosphate is obtained. After the dihydrate iron phosphate is calcined, high-purity battery-grade anhydrous iron phosphate is obtained.
2. The method for preparing battery-grade iron phosphate using a surfactant according to claim 1, characterized in that: In the step S1, the concentration of phosphorus in the phosphate solution is 0.8-1.4 mol / L; the phosphate solution is prepared from ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, phosphoric acid, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate.
3. The method for preparing battery-grade iron phosphate using a surfactant according to claim 1, characterized in that: In step S1, the concentration of iron in the ferrous salt solution is 0.8-1.3 mol / L; the ferrous salt solution is prepared from ferrous sulfate, ferrous nitrate, ferrous chloride, iron powder and iron sheet.
4. The method for preparing battery-grade iron phosphate using a surfactant according to claim 1, characterized in that: In the step S2, the mass ratio of the added ferrous salt to the CTAB in the ferrous salt solution and the CTAB aqueous solution is 100-200:
1.
5. The method for preparing battery-grade iron phosphate using a surfactant according to claim 1, characterized in that: In step S2, concentrated sulfuric acid is used to adjust the pH of the ferrous salt solution to 2.0-2.
5.
6. The method for preparing battery-grade iron phosphate using a surfactant according to claim 1, characterized in that: In step S3, concentrated ammonia water is used to adjust the pH of the phosphate solution to 6.0-8.0; the molar ratio of the added hydrogen peroxide to the ferrous element in the ferrous salt solution is controlled to be 0.6-0.8:
1.
7. The method for preparing battery-grade iron phosphate using a surfactant according to claim 1, characterized in that: In the step S4, the phosphorus-oxygen mixed solution is added within 30-60 minutes; the molar ratio of iron element to phosphorus element in the ferrous salt and CTAB mixed solution and the phosphorus-oxygen mixed solution is 1:0.9-1.
1.
8. The method for preparing battery-grade iron phosphate using a surfactant according to claim 1, characterized in that: In the step S5, the conductivity of the washing water of the slurry A after preliminary filtration and washing is ≤2000 μS / cm.
9. The method for preparing battery-grade iron phosphate using a surfactant according to claim 1, characterized in that: In the step S6, the molar ratio of phosphorus in the phosphoric acid solution to iron in the slurry A solution should be controlled to be n(P):n(Fe)=0.1-0.5:1; The heating time is controlled at 90-110 min; the mass ratio of the pure water to the filter cake is 1.2-1.8:
1.
10. The method for preparing battery-grade iron phosphate using a surfactant according to claim 1, characterized in that: In the step S7, the conductivity of the washing water after the slurry B is filtered and washed needs to be ≤400 μS / cm.
Citation Information
Patent Citations
Iron phosphate as well as preparation method and application thereof
CN118324108A
Preparation method of iron phosphate precursor adaptive to high-compaction lithium iron phosphate
CN118702083A